2010
DOI: 10.1111/j.1540-8159.2010.02765.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure of Patient and Physician during Implantation and Upgrade of Cardiac Resynchronization Devices

Abstract: In patients, incipient deterministic radiation effects can theoretically be observed at dose area product >400 Gy*cm(2), a dose applied in 2.9% of CRT implantation procedures. Special follow-up programs are considered necessary for these patients and for operators, as the latter may be exposed over many years given the unknown long-term impact of chronic radiation exposure and the nature of current complex electrophysiology and device procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 26 publications
(44 reference statements)
4
33
0
4
Order By: Relevance
“…In the last 10 years, however, the issue of radiation exposure in interventional cardiology and electrophysiology has risen, and the “linear no‐threshold” model (which assumes that no safe dose exists and that the risk increases linearly with exposure) has been accepted by the majority of scientists . The radiation risk is particularly high for CRT implanting physicians, and a conservative recommendation to perform a maximum of 4 CRT implantations per month per implanter has been advocated …”
Section: Discussionmentioning
confidence: 99%
“…In the last 10 years, however, the issue of radiation exposure in interventional cardiology and electrophysiology has risen, and the “linear no‐threshold” model (which assumes that no safe dose exists and that the risk increases linearly with exposure) has been accepted by the majority of scientists . The radiation risk is particularly high for CRT implanting physicians, and a conservative recommendation to perform a maximum of 4 CRT implantations per month per implanter has been advocated …”
Section: Discussionmentioning
confidence: 99%
“…They also have shown that this exceed threshold dose for the induction of skin effects [10]. An other study addressing the operator's side of the problem demonstrated that the radiation exposure of the hands is approximately 9.2 mSv, and the other part of the body as 1.2 mSv [11].…”
Section: Discussionmentioning
confidence: 99%
“…wynika, że procedury upgrade do CRT cechują się istotnie wyższymi wartościami analizowanych parametrów w porównaniu z modernizacjami niezwiązanymi z resynchronizacją [26]. W przypadku analizowanych relacji grup zabiegów CRT: de novo vs upgrade, zarówno średnie TFTs, jak i DAP były zbliżone.…”
Section: Omówienieunclassified
“…W przypadku analizowanych relacji grup zabiegów CRT: de novo vs upgrade, zarówno średnie TFTs, jak i DAP były zbliżone. Podobnie jak u innych autorów nie stwierdzono statystycznie istotnej różnicy między badanymi wielkościami TFTs i DAP [26,27]. W sytuacji zabiegów CRT zwraca uwagę znaczący udział w dawce skumulowanej trybu HLF (do 67%), 3-krotnie większy w porównaniu z wartościami średnimi dla procedur konwencjonalnych.…”
Section: Omówienieunclassified